2022
DOI: 10.1109/tits.2021.3095897
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Resilience of Transportation Systems: Is a Traffic Jam About to Occur?

Abstract: Measurement of traffic flow stability and resilience is a critical step toward evaluating the performance of transportation systems and implementing appropriate management strategies. Quantifying changes in the stability and resilience of transportation systems, however, is hampered by the complexity of real traffic dynamics and the diversity of infrastructures. Here, we demonstrate that changes in traffic flow stability and resilience are signaled by generic features, known as early warning signals in the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Data-driven prediction methods have also offered a solution to the formidable challenge of predicting catastrophic events in a variety of complex systems. Recent studies have shown that features extracted from data can be used to predict critical transitions [165] and extreme events [166] in the dynamics of a variety of complex systems, including aeroelastic systems [39,40,44,167,168], ecological systems [51,[169][170][171][172][173][174][175], epidemiological systems [176][177][178][179], traffic flow systems [158,180] and fluid flows [166,[181][182][183].…”
Section: Introductionmentioning
confidence: 99%
“…Data-driven prediction methods have also offered a solution to the formidable challenge of predicting catastrophic events in a variety of complex systems. Recent studies have shown that features extracted from data can be used to predict critical transitions [165] and extreme events [166] in the dynamics of a variety of complex systems, including aeroelastic systems [39,40,44,167,168], ecological systems [51,[169][170][171][172][173][174][175], epidemiological systems [176][177][178][179], traffic flow systems [158,180] and fluid flows [166,[181][182][183].…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent congestion has temporal periodicity and high spatial similarity, which is caused by insufficient infrastructure supply (An et al 2016). Previous studies have confirmed that traffic congestion is the result of instability and phase transition in the traffic flow dynamics (Ghadami et al 2022). To analyse the characteristics of traffic congestion, the traffic flow is abstracted into TSP (Lan et al 2008).…”
Section: Introductionmentioning
confidence: 99%